The Political Dynamics of Space Behind the Jakarta–Bandung High-Speed Rail (Whoosh) Megaproject Development - Mumtaz, Sarah (PCD Journal, 2024)
This paper explores the Jakarta–Bandung High-Speed Rail (HSR) megaproject, which began in 2016 and was completed in 2023. Currently, the high-speed train, known as "Whoosh," operates, connecting Jakarta and Bandung in just 30 minutes. The project highlights the competition between China and Japan in asserting their leadership in Asia's infrastructure investments. Under China's Belt and Road Initiative (BRI), the financing for this HSR project was sourced 75% from the China Development Bank, with the remaining 25% contributed from an Indonesian consortium. This study seeks to examine the impacts of the Indonesia—China HSR construction and analyze them through Henri Lefebvre’s Theory of the Production of Space (1991). The HSR requires space that it passes as well as train stations it stops. The location around train stations later transformed into a new economic zone. Thus HSR created physical and social spaces, including the process of meaning-making and control over representational of space. Using a qualitative approach, the study finds that the project has triggered significant spatial changes, transforming previously low-economic-value areas into high-value (capitalist) zones, marked by the dominance of capital owners and resource control, ultimately leading to conflicts over land rights at the community level. Global capital actors play a crucial role in the space shaping and making, and transportation technology serves as a entry point strategy.